Factors influence performance of export in 5 selected ASEAN countries: a panel data analysis / Nuridayu Abd Rahim - Abd Rahim, Nuridayu (Faculty of Business and Management, 2018)
Exports play an important role in economy, the main objectives of this study are to determine the relationship between level of exports with gross domestic products, imports, inflation rate, foreign direct investment and exchange rate. Next, to identify the most significant variable that affects the exports performances in 5 selected ASEAN countries out of 10 ASEAN members included Singapore, followed by Malaysia, Vietnam, Philippines and Indonesia. Due to that, by using data from World Development Indicators this study conducted panel data analysis for the period of 1996 to 2017 and consider Gross Domestic Product, Imports, Inflation, Exchange Rate and Foreign direct investment as independent variables. The final model results show that Gross Domestic Product, Import and Inflation ended with positive relationship with export performance. Opposite that, exchange rate was found to negatively impact on export performance. While foreign direct investment was found to insignificantly relate with export performance. Following that, suggested as recommendations, idea for future researcher are to widening or narrowing the scope or area of study. And to adding any related macroeconomic variables to the study.